Co-SLD suppressed the growth of oral squamous cell carcinoma via disrupting mitochondrial function. Issue 1 (4th December 2019) - Li, Sirui; Li, Guo; Zhang, Taofeng; Li, Jili; Zhao, Quanyi; Zhang, Baoping; Wang, Rui; Zhou, Rong; Si, Jing; Gan, Lu; Liu, Yang; Zhang, Hong; et al.
Abstract: To evaluate the safety and efficacy of novel cobalt complex with sulindac (Co-SLD), the zebrafish and oral squamous cell carcinoma CAL27 were investigated in the present study. The developmental toxicity of Co-SLD ranging from 5 to 20 μM was determined by exposure to 3–144-h post-fertilization (hpf) zebrafish. Our data showed that Co-SLD did not cause to the appreciable toxicity at low concentration (5 and 10 μM). A remarkable toxicity was observed at high concentration (20 μM), including increased mortality and malformation, delayed hatchability, reduced heart rate as well as suppressed behaviour. With regard to the antitumor activity of Co-SLD, inhibited cell growth and migration capability were outstandingly observed in oral squamous cell carcinoma treated with 10 and 20 μM Co-SLD, which could be mainly attributed to the Co-SLD-elicited mitochondrial damage as marked by the depression of mitochondrial membrane potential, ROS accumulation and ATP depletion. Furthermore, administration of 10 μM Co-SLD was an optimal concentration not only to avoid the normal tissue toxicity, but also to enhance the killing of cancer cells via disrupting mitochondrial dysfunction. Taken together the above results demonstrated the desirable response of oral squamous cell carcinoma to Co-SLD.